The Impact of Urban Development on Tourism Development - Allaqulovich, Allanov Kilich; Kadyrovich, Choriev Abdikayim; oglu, Odilov Saloxitdin Abdulaziz (Indonesian Journal of Innovation Studies, 2022)
This article provides information on the impact of urban development on tourism development in Uzbekistan, especially the tourist potential of large cities, the peculiarities of the reception of tourists, tourist facilities and tourism industries. The share of tourism in the gross domestic product (GDP) of Uzbekistan, the population employed in this field, as well as the work to be done in the future to further develop this sector are scientifically covered.